2019
DOI: 10.1111/jpm.12540
|View full text |Cite
|
Sign up to set email alerts
|

“I felt some prejudice in the back of my head”: Nursing students’ perspectives on learning about mental health from “Experts by Experience”

Abstract: Accessible Summary What is known on the subject? Consumer participation in mental health services is embedded in mental health policy in many countries. The negative attitudes of nurses and other health professionals to consumer participation poses a significant obstacle to this policy goal Involving mental health “Experts by Experience” in the education of nursing students demonstrates positive attitudinal change What this paper adds to existing knowledge? More detailed understanding of nursing students… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 58 publications
1
34
0
Order By: Relevance
“…Third, nursing students reported changes and new experiences regarding mental health nursing education compared to how they experienced the traditional education on the topic [ 16 , 25 , 27 , 30 , 32 , 33 , 34 ]. Education using consumer involvement led to changes in students’ approaches to practice, their self-awareness, reflection, and empathy; it also promoted a more in-depth understanding of the learning contents by encouraging them to recall their past experiences with their families and acquaintances and relate to what they discussed in their classes, thinking about the mental-health-related problems of those around them.…”
Section: Resultsmentioning
confidence: 99%
“…Third, nursing students reported changes and new experiences regarding mental health nursing education compared to how they experienced the traditional education on the topic [ 16 , 25 , 27 , 30 , 32 , 33 , 34 ]. Education using consumer involvement led to changes in students’ approaches to practice, their self-awareness, reflection, and empathy; it also promoted a more in-depth understanding of the learning contents by encouraging them to recall their past experiences with their families and acquaintances and relate to what they discussed in their classes, thinking about the mental-health-related problems of those around them.…”
Section: Resultsmentioning
confidence: 99%
“…2017; Happell et al . 2019b; Hornik‐Lurie et al, 2018). Quantitative studies have demonstrated substantial attitudinal change, including a decrease in stigmatized views towards people with mental illness following the experience of being taught by EBE (Happell et al .…”
Section: Discussionmentioning
confidence: 99%
“…For example, mental health literacy and accurate knowledge about managing mental illness can be offered to the public through different avenues: public and private media, movies, citizen education, government and mental healthcare practitioner collaboration with affected families and community health centres. Mental healthcare professionals must also be properly educated to preclude their stigmatization of people diagnosed with mental illness Happell et al (2019). found that nursing students being taught mental health by an Expert by Experience (consumer) have improved understanding and perspectives of mental illness, which leads to improved learning experiences.…”
mentioning
confidence: 99%